A Case Study of Honest Character Development in Early Childhood in Bengkulu City - Haroswinarti, Kimli; Sasongko, Rambat Nur; Kristiawan, Muhammad; Mentari, Eca Gesang (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2021)
The character gap is very dangerous and can occur if communication and hanging out together no longer exist in the community environment. This study aims to analyze the character development of honesty in early childhood group B PAUD Fatma Kenanga Bengkulu City. The descriptive qualitative type of survey was used as a research method, involving 21 children of group B PAUD Fatma Kenanga Bengkulu City in the 2016/2017 academic year. Data were collected through observations to measure the honesty character of children carried out by classroom and central teachers using a Likert scale, then analyzed using the average formula. The results of the study concluded that the development of honest character in PAUD group B PAUD Fatma Kenanga Bengkulu City had developed well, especially in the indicators of private property. Meanwhile, some other honest character developments show the behavior of children who are just starting to develop them. The implication of this research shows that the honest character of children makes children more independent and pious, therefore character education for children needs to be paid attention to so that the nation and state can advance.